The Relationship between the Genetic Polymorphisms of Interleukin-33 (IL-33) and Interleukin-1 Receptor-Like 1 (IL1R1) with the Levels of Interleukin-33 in Patients with Asthma and Multiple Sclerosis - Maryam Ahmadi; Nahid Eskandari; Fereshteh Ale-Sahebfosoul; Mansour Salehi; Ramin Ghasemi (مجله دانشکده پزشکی اصفهان, 2016)
Background: Recent evidence suggests that the interleukin-33/interleukin-1 receptor-like 1 (IL-33/IL1RL1) axis plays a critical role in autoimmune and inflammatory disorders; however, its mechanistic role in these diseases has not been clearly defined. The present study aimed to investigate the frequency of rs1342326 polymorphism of IL-33 gene and rs10204137 polymorphism of IL1RL1 gene with serum levels of IL-33 in multiple sclerosis (MS), asthma and healthy subjects In Isfahan Province, Iran.